Impact of seed rate and time of sowing on rice fallow crops and their sustainable production system in machine-harvested rice fields - Jaya Singh, Devi Geethika; Elangovan, Subramanian; Paramasivam, Arunachalam; Arumugam, Gurusamy; Basir Ahmed, Bhakiyathu Saliha; Gurunathan, Selvarani; Krishnan, Jothilakshmi; Arumugam, Sathishkumar (Frontiers in Sustainable Food Systems, 2024)
The primary objective of this study was to identify the optimal seed rate and time of sowing rice fallow crops in machineharvested rice fields. Rice fallow crop cultivation is the most significant low-cost production system in the delta region. The sustainability of the system is uncertain in the context of mechanical harvesting of rice using heavy machinery. The crops selected for the experimental trial were blackgram (Vigna mungo L. Hepper.), sesame (Sesamum indicum) and prosomillet (Panicum miliaceum). The field experiment was conducted using a strip plot design. The rice fallow crops were arranged in vertical plots, while various seed rates and times of sowing were arranged in horizontal plots. The results indicated that the sowing time and seed rate significantly influenced the growth and development of rice fallow crops in machineharvested rice fields. Among the blackgram treatments, a 20% increase in the seed rate (36 kg ha -1 ) on the day of rice harvest resulted in greater grain and straw yield. An increased seed rate compensated for the damage caused by mechanical harvesting on the day of harvest when the combine harvester was utilized, which enhanced the yield and sustainability of the rice fallow crops.